Knowledge and Caring Attitude of Sri Lankan Nurses in Providing Care for Dying Patients ? A Cohort Study - M.M Rajudeen; M. Janoof; P Dioso (Universitas Gadjah Mada, 2016)
This research identified evidence of knowledge and caring attitude among Sri Lankan nurses caring for dying patients; and identified the factors affecting nursing care for the dying in the eastern province of Sri Lanka. A quantitative cohort study design was used having questionnaires as the means of collecting the data. The purposive way of sampling selected 120 staff nurses employed in a government hospital as respondents who falls under the inclusion and exclusion criteria.There was significant evidence of caring attitude towards the dying (p = 0.005534) and knowledge on the end-of-life nursing care (p = 0.0004703) for the dying patients. Educational attainment (p = 0.050001), clinical experiences (p = 0.01499), age (p = 0.01061) and civil status (p = 0.001782) were factors affecting the knowledge and attitude of Sri Lankan nurses in delivering nursing care for the dying patients admitted to a government hospital.